FDG avid breast cancer bone metastases silent on CT and scintigraphy: a case report with radiologic-pathologic correlation. (October 2017) - Jeong, Daniel; Bui, Marilyn; Peterson, Daniel; Montilla-Soler, Jaime; Gage, Kenneth L
Bone is the one of the most common distant metastatic sites in breast cancer. Routine initial breast cancer staging evaluation typically includes computed tomography (CT) and skeletal scintigraphy while 18F fluorodeoxyglucose (FDG) positron emission tomography-computed tomography (PET-CT) is reserved for clinically high-risk cases. Since FDG PET-CT is not routinely performed during staging or surveillance evaluations, it is important for radiologists and clinicians to appreciate the limitations of bone metastasis detection on CT and scintigraphy. We present a case of bony metastases of invasive ductal carcinoma of the breast which were not detected on diagnostic CT or skeletal scintigraphy but were metabolically active on FDG PET-CT and evident on magnetic resonance. We provide a review of the literature and radiologic–pathologic correlation to explain the discordant imaging findings.